Comparison of beam segment versus full plan re-optimization in daily magnetic resonance imaging-guided online-adaptive radiotherapy. (January 2021) - van Timmeren, Janita E.; Chamberlain, Madalyne; Krayenbuehl, Jérôme; Wilke, Lotte; Ehrbar, Stefanie; Bogowicz, Marta; Zamburlini, Mariangela; Garcia Schüler, Helena; Pavic, Matea; Balermpas, Panagiotis; Ryu, Chaehee; Guckenberger, Matthias; et al.
Abstract: The optimal approach for magnetic resonance imaging-guided online adaptive radiotherapy is currently unknown and needs to consider patient on-couch time constraints. The aim of this study was to compare two different plan optimization approaches. The comparison was performed in 238 clinically applied online-adapted treatment plans from 55 patients, in which the approach of re-optimization was selected based on the physician's choice. For 33 patients where both optimization approaches were used at least once, the median treatment planning dose metrics of both target and organ at risk differed less than 1%. Therefore, we concluded that beam segment weight optimization was chosen adequately for most patients without compromising plan quality.